SOCIO ECONOMIC PROFILE OF WOMEN RUN ENTERPIRSES OF MSMES IN VISAKHAPATNAM CITY - Lakshmi, V. Gowri; Kasthuri, G.V.K. (International Journal of Psychosocial Rehabilitation, 2020)
Entrepreneurship is considered as one of the most important factors contributing to the economic development of the society. Entrepreneurs have been considered instrumental in initiating and sustaining socio economic development. There is an evidence to believe that countries which have proportionately higher percentage of entrepreneurs in their population have developed much faster as compared to countries, which have lesser percentage of them in the society. They discover new sources of supply of materials and markets and establish new and more effective forms of organization. Entrepreneurs perceive new opportunities and seize them with super normal will power and energy, essential to overcome the resistance that social environment offers. Development of entrepreneurship among women is a major step to increase women participation in the process of economic development. It will speed up economic growth, and provide employment opportunities for women resulting in improving the economic independence. Provision of economic opportunities for women can also improve the social, educational and health status of women and their families. Entrepreneurship development among women can be considered as a possible approach to economic empowerment of women. In this paper studies about the socio economic profile of women entrepreneurs of Micro small and medium enterprises which in Visakhapatnam city.